Fenótipo da fragilidade ou sarcopenia de acordo com o EWGSOP2: qual o melhor preditor do risco de morte e incapacidade em pessoas idosas? - Canelada, Aline Fernanda de Souza (Universidade Federal de São Carlos, 2024)
Introduction: The central component of both frailty and sarcopenia is the decline of neuromuscular function and both conditions have been associated with an increased risk of disability and death. Despite being distinct conditions, frailty and sarcopenia often coexist in older people and both require the assessment of gait speed and grip strength. However, there is a question with regards to which would be better for identifying the risk of disability and mortality. Moreover, it is possible that one of the components of these two constructs could be better than the complete construct at identifying the risk of disability and the different cut-off points for grip strength proposed in the literature could affect the association with the risk of mortality. Objectives: The present theses has two objectives: 1) To compare the frailty phenotype and sarcopenia construct (EWGSOP2) using different cut-off points for defining low strength and identify which is better at identifying the risk of mortality in individuals ≥ 60 years of age over a 14-year follow-up period; and 2) Compare frailty, sarcopenia and their respective components to determine which best identifies the risk of disability on basic and instrumental activities of daily living (BADL and IADL, respectively). Methods: Data were collected on participants of the English Longitudinal Study of Ageing ≥ 60 years of age. A total of 4,597 individuals were considered in the analysis of the risk of mortality, whereas 3,637 and 3,696 individuals without disability on BADL and IADL, respectively, at baseline were considered in the analysis of functional decline. Frailty was defined by the phenotype and sarcopenia was defined based on the EWGSOP2 criteria. In the analysis of mortality, different grip strength cut-off points were used to define low strength (< 36, < 32, < 30, < 27 and < 26 kg for men and < 23, < 21, < 20 and < 16 kg for women). In the analysis of disability, only one cut-off point was used: < 27 kg for men and < 16 kg for women. In both analyses, low skeletal muscle mass index (< 9.36 kg/m2 for men and < 6.73 kg/m2 for women) and low physical performance (gait speed ≤ 0.8 m/s) were added to the sarcopenia construct. In the analysis of disability, the complete frailty and sarcopenia constructs were considered as well as each of the respective components analyzed individually. Adjusted Cox models were used for the survival analyses and adjusted Poisson mixed models were used to analyze the incidence of disability in eight years. Results: To identify the risk of death, sarcopenia with a grip strength cut-off point of < 36 kg for men and < 23 kg for women was best (severe sarcopenia: 62%; versus frail: 49%) compared to frailty and other cut-off points to define low strength. With regards to disability, low physical performance (annual risk of 12% on BADL and 14% on IADL) assessed by gait speed ≤ 0.8 m/s was as effective as frailty (annual risk of 27% on BADL and 28% on IADL) for the assessment of the incidence of functional decline. Conclusions: The sarcopenia construct using a grip strength cut-off point of < 36 kg for men and < 23 kg for women for the definition of low strength was the best predictor of mortality, whereas the low physical performance component only (gait speed ≤ 0.8 m/s) was as effective as the frailty phenotype at identifying functional decline.
Frailty phenotype or sarcopenia according to the EWGSOP2: which is a better indicator of mortality risk and disability in older adults?
Keywords: Fragilidade; Sarcopenia; Fraqueza; Baixa força muscular; Lentidão; Sobrevida; Declínio funcional; CIENCIAS DA SAUDE::SAUDE COLETIVA::EPIDEMIOLOGIA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA